Show-ha shoten! Volume 5 - Asakura, Akinari, 1989- (Shonen Jump manga., 2024)
"By winning the preliminary round, Azemichi and Taiyo have officially qualified for the Wara-1 Koshien comedy competition! Rumor has it that everyone who's ever gotten advice from the eccentric Professor Hiyama has gone on to win Wara-1 Koshien--but the only way to get that advice is to win the Hiyama Cup! Can Azemichi and Taiyo beat both Broken Glass Slipper and Shiba Inu World Tour to win a meeting with the comedy legend?"--